2021
DOI: 10.1136/bmjdrc-2020-001551
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipidomics profile in pregnancy and gestational diabetes risk: a prospective study in a multiracial/ethnic cohort

Abstract: IntroductionDisruption of lipid metabolism is implicated in gestational diabetes (GDM). However, prospective studies on lipidomics and GDM risk in race/ethnically diverse populations are sparse. Here, we aimed to (1) identify lipid networks in early pregnancy to mid-pregnancy that are associated with subsequent GDM risk and (2) examine the associations of lipid networks with glycemic biomarkers to understand the underlying mechanisms.Research design and methodsThis study included 107 GDM cases confirmed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…The decrease in SMs’ 14:0, 15:0, 16:1, and 22:0 indicates dysregulated sphingolipid metabolism. Past early-pregnancy GDM studies have noted SMs to be lower in GDM cases compared to non-GDM cases ( Furse et al, 2019 ; Rahman et al, 2021 ), and a study by Lai et al found decreased SM levels in women with GDM to be associated with increased risk of developing type 2 diabetes ( Lai et al, 2020 ). Sphingomyelins may play an indirect role in impaired insulin signaling, as increased levels of ceramides, a sphingolipid that can be derived from sphingomyelins, have been reported to inhibit the insulin signaling pathway, while also disturbing mitochondrial respiration ( Roszczyc-Owsiejczuk & Zabielski, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in SMs’ 14:0, 15:0, 16:1, and 22:0 indicates dysregulated sphingolipid metabolism. Past early-pregnancy GDM studies have noted SMs to be lower in GDM cases compared to non-GDM cases ( Furse et al, 2019 ; Rahman et al, 2021 ), and a study by Lai et al found decreased SM levels in women with GDM to be associated with increased risk of developing type 2 diabetes ( Lai et al, 2020 ). Sphingomyelins may play an indirect role in impaired insulin signaling, as increased levels of ceramides, a sphingolipid that can be derived from sphingomyelins, have been reported to inhibit the insulin signaling pathway, while also disturbing mitochondrial respiration ( Roszczyc-Owsiejczuk & Zabielski, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the study by Bao et al [25], we found that elevated lipid levels in the middle of pregnancy, especially TG levels, were associated with the risk of GDM. In addition, Daniel et al and Mohammad et al examined that elevated maternal TG levels in early pregnancy were associated with the risk of GDM [9,10]. Yazıcı et al demonstrated that increased lipid levels and altered intracellular signaling metabolism have been associated with insulin resistance, which is mediated by different pathways, such as the novel protein kinase c pathway and the JNK-1 pathway [26].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, maternal age, obesity, pre-pregnancy body mass index (BMI), and polycystic ovary syndrome (PCOS) history have been generally regarded as the risk factors for GDM [7]. Recent studies have also suggested that abnormal maternal lipid metabolism, especially elevated triglycerides, served as a risk factor for the development of GDM [8][9][10][11]. Actually, the appropriate increase of maternal triglycerides (TG) and cholesterol during pregnancy, considered as a physiological adaptation, has positive impact on the maintenance of pregnancy and fetal growth [7].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics is a powerful tool in biomarker discovery and holds great promise for precision medicine ( Peng et al, 2015 ; Burgess, 2021 ; Schmidt et al, 2021 ). Targeted metabolomics is common in studies exploring human health questions that range from aging ( Jones et al, 2012 ; Hastings et al, 2019 ) to complex diseases ( Lewis et al, 2008 ; van der Sijde et al, 2014 ; Menni et al, 2017 ; Barupal et al, 2018 ; Rahman et al, 2021 ; Sindelar et al, 2021 ). An advantage of untargeted metabolomics for these questions is the ability to reach beyond sets of well-studied compounds to explore differences in an unbiased way ( Cajka and Fiehn, 2016 ).…”
Section: Introductionmentioning
confidence: 99%